2015
DOI: 10.3109/09537104.2015.1021319
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of soluble C-type lectin-like receptor 2 in human plasma

Abstract: Detection of platelet activation in vivo is useful to identify patients at risk of thrombotic diseases. Platelet factor 4 (PF4) and β-thromboglobulin (β-TG) are used for this purpose; however, they are easily released upon the minimal platelet activation that occurs during sampling. Soluble forms of several platelet membrane proteins are released upon platelet activation; however, the soluble form of C-type lectin-like receptor 2 (sCLEC-2) has not yet been fully investigated. Western blotting with an anti-CLEC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 26 publications
1
21
4
Order By: Relevance
“…Treatment with the CLEC-2 mAb INU1 achieves sustained depletion of CLEC-2 from mouse platelets in vivo (60) due to internalization and intracellular degradation (61), and severe but transient thrombocytopenia. CLEC-2, however, is not shed from activated platelets, and only very low levels of the CLEC-2 ectodomain are present in blood (62). CLEC-2-positive microvesicles are elevated in the plasma of patients with rheumatoid arthritis (23).…”
Section: Gpvimentioning
confidence: 99%
“…Treatment with the CLEC-2 mAb INU1 achieves sustained depletion of CLEC-2 from mouse platelets in vivo (60) due to internalization and intracellular degradation (61), and severe but transient thrombocytopenia. CLEC-2, however, is not shed from activated platelets, and only very low levels of the CLEC-2 ectodomain are present in blood (62). CLEC-2-positive microvesicles are elevated in the plasma of patients with rheumatoid arthritis (23).…”
Section: Gpvimentioning
confidence: 99%
“…It has been known that CLEC-2 is released from activated platelet as a soluble form by shedding. 33 Therefore, we also investigated the possibility that soluble CLEC-2 is involved in a megakaryocyte expansion associated with BM FRC-like cells. We compared the megakaryocyte expansion in coculture with BM FRC-like cells in the presence or absence of GM6001 and GM6001.…”
Section: Bm Frc-like Cells Augment Megakaryocyte Expansion Through CLmentioning
confidence: 99%
“…Atherosclerotic lesion formation is the main cause of atherosclerotic diseases. In addition, Kazama et al [21] showed a trend towards an increase in soluble pCLEC-2 concentration in DM patients, who are a high-risk population for stroke. However, the mechanisms underlying the association between pCLEC-2 and death or recurrence of vascular diseases are still unclear and more studies, especially animal experiments, are needed to explore them.…”
Section: Discussionmentioning
confidence: 99%